The Influence of Corporate Governance on the Disclosure of Sustainability Reports with Profitability as a Moderating Variable - Pramita, A. A. Sri; Budiasih, I Gusti Ayu Nyoman (Dinasti Publisher, 2025)
This study aims to examine the influence of corporate governance on sustainability report disclosure, with profitability as a moderating variable. The sample for this study consists of Indonesian companies listed in the ASRRAT rankings for the 2018-2023 period. The sample was selected using the purposive sampling method, resulting in 22 companies with a total of 132 observations. Data were analyzed using moderated regression analysis. The findings of this study indicate that the independent board of commissioners does not affect sustainability report disclosure. The audit committee has a positive influence on sustainability report disclosure. Meanwhile, profitability does not moderate the effect of the independent board of commissioners and the audit committee on sustainability report disclosure.